Desain Perencanaan Pembelajaran Pendidikan Pancasila dan Kewarganegaraan (PPKn) Bermuatan Karakter Siswa SD Negeri 07 Woja - Julkifli; Sofyan Syamratulangi (CV. ULIL ALBAB CORP, 2024)
Character is a serious concern for all components of education, because recently there have been frequent cases of immoral acts carried out by society, especially students themselves, so that in every scope of education units must be able to design and implement a curriculum with character. The purpose of this research is to determine the design of learning planning for Pancasila and citizenship education containing character. The research method used in this research uses a qualitative descriptive research design, namely a phenomenological type of research. The research subjects were school principals, teachers and students. Miles and Huberman data analysis: data collection, data reduction, data presentation, and verification/ drawing conclusions. The research results show that the design of the Pancasila and Citizenship Education learning plan takes the form of a learning implementation plan based on the curriculum, the use of visual media and the provision of teaching materials based on learning indicators, the assessment includes affective, cognitive and skills aspects according to the student's character based on the 2013 curriculum. In conclusion, the design of the Pancasila and citizenship education learning plan has shown character content, namely learning implementation plans, use of media, provision of teaching materials and assessment according to student character based on the 2013 curriculum.